Collaboration with Kenyan and Tanzanian publishers: two practical booklets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
With CTA's support, Friends of the Book Foundation and Stantex Publishers, based in Nairobi (Kenya), recently co-published English versions of the following two booklets originally produced in Kiswahili by the Kagera Writers and Publishers...